Metabolic interplay in a synthetic consortium: insights into the mediating role of a minority species - Backes, Cassandra; Ranava, David; Infossi, Pascale; Delecourt, Louis; Roger, Magali; Giudici-Orticoni, Marie-Thérése (Frontiers in Microbiology, 2026)
Microbial interactions are pivotal components of Earth's ecosystems, driving essential processes that sustain life, regulate environmental conditions, and ensure ecosystem resilience. A comprehensive understanding of these relationships is imperative for leveraging their potential in environmental solutions and biotechnological innovations. In this study, we explore the intricate bacterial interplay between three key players involved in biomass degradation: Clostridium acetobutylicum (Gram-positive), Escherichia coli, and Nitratidesulfovibrio vulgaris Hildenborough (Gram-negative) using synthetic reconstituted consortium. N. vulgaris independently cooperates with both C. acetobutylicum and E. coli through thigh physical interactions and transfer of biological material to ensure its survival. These interactions are dependent of nutritional starvation and provokes with a rise of hydrogen production in the consortium C. acetobutylicum/N. vulgaris. However, prior studies showed that E. coli does not exchange cytoplasmic material with C. acetobutylicum. To probe the stability of these microbial interactions and the hydrogen production, we monitored growth and metabolic kinetics in pure and co-cultures. Our findings reveal a surprising shift: N. vulgaris emerges as an unexpected mediator and protector, reshaping the relationship between E. coli and C. acetobutylicum. This study highlights the underestimated influence of minority species like N. vulgaris in microbial communities, shedding a new light on their ecological and functional roles.